2013
DOI: 10.1371/journal.pone.0078749
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of DNA Extraction for Detection of Mycobacteria in Tissues

Abstract: BackgroundNucleic acid-based methods offer promise for both targeted and exploratory investigations of microbes in tissue samples. As the starting material for such studies is a mixture of host and microbial DNA, we have critically evaluated the DNA extraction step to determine the quantitative and qualitative parameters that permit faithful molecular detection of mycobacteria in infected tissue. Specifically, we assessed: 1) tissue disruption procedures; 2) DNA extraction protocols; and 3) inhibition of bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…On the other hand, F57, a single copy-segment, has demonstrated high specificity for the detection of MAP (Coetsier et al, 2000;Ellingson et al, 2000;Harris and Barletta, 2001;Strommenger et al, 2001;Vansnick et al, 2004;Rajeev et al, 2005). The nested IS900 assay can detect 0.01 pg of DNA (corresponding to 10 genomes) when extracted from a pure culture, while the F57 assay can detect 0.1 pg of DNA (corresponding to 100 genomes; Radomski et al, 2013). Vansnicka et al (2004), Tasara and Stephan (2005), and Schönenbrücher et al (2008) recommend including the F57-PCR assay to confirm the presence of MAP after a positive IS900-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, F57, a single copy-segment, has demonstrated high specificity for the detection of MAP (Coetsier et al, 2000;Ellingson et al, 2000;Harris and Barletta, 2001;Strommenger et al, 2001;Vansnick et al, 2004;Rajeev et al, 2005). The nested IS900 assay can detect 0.01 pg of DNA (corresponding to 10 genomes) when extracted from a pure culture, while the F57 assay can detect 0.1 pg of DNA (corresponding to 100 genomes; Radomski et al, 2013). Vansnicka et al (2004), Tasara and Stephan (2005), and Schönenbrücher et al (2008) recommend including the F57-PCR assay to confirm the presence of MAP after a positive IS900-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PCR sensitivity can be affected by the inhibitors present in the clinical samples, those from the reagents used in the extraction method, or the amount of extracted DNA (CARDOSO et al, 2009;RADOMSKI et al, 2013). Cardoso et al (2009) demonstrated that the potential effect of PCR inhibitors can be reduced by diluting (1:2) or increasing the amount of DNA in the samples.…”
Section: Discussionmentioning
confidence: 99%
“…The application of molecular methods on clinical specimens encounters a number of problems, including a complex mycobacterial cell wall, the presence of the bacterial cell within a phagosome, a host cell and a granuloma, and the low amount of bacterial cells or DNA (KUMAR et al, 2010;RADOMSKI et al, 2013). Additionally, inhibitory substances present in the samples or the reagents used during DNA extraction, and an excessive amount of host DNA compared to the target DNA of the pathogen, also make accurate pathogen detection in clinical specimens difficult (PARK et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most of the amplification-based assays described for detecting MTC nucleic acids directly in fresh or formalin-fixed paraffin-embedded animal tissues only yield a moderate sensitivity, usually up to 75% when compared to the reference bacteriological culture, particularly when testing tissues without the characteristic lesions (Liébana et al, 1995 ; Coetsier et al, 2000 ; Roring et al, 2000 ; Taylor et al, 2001 , 2007 ; Parra et al, 2008 ; Thacker et al, 2011 ). This limitation is mostly related to the increased complexity for disrupting and recovering genomic DNA from the tough mycobacterial cells, which harbor complex walls, and to the inefficiency of the extraction procedures from affected animal tissues, especially those exhibiting strong fibrosis, calcification, and with no histological evidence of acid-fast bacteria (Liébana et al, 1995 ; Taylor et al, 2007 ; Amaro et al, 2008 ; Parra et al, 2008 ; Costa et al, 2013a ; Radomski et al, 2013 ). The presence of amplification inhibitors in crude tissue extracts, and of large amounts of co-extracted host eukaryotic DNA, often represent an additional problem.…”
Section: Major Challenges Of Tuberculosis Nucleic Acid Testingmentioning
confidence: 99%